Evaluation of biochar combustion reactivity under pyrolysis temperature: Microstructure characterization, kinetics and thermodynamics. Issue 5 (October 2020) - Tong, Wei; Cai, Zelong; Liu, Qingcai; Ren, Shan; Kong, Ming
Highlights: Combustion of Ficus virens char under different pyrolysis temperature are studied. Chemical and physical characteristics of biochar are given. Estimated values of activation energy from FWO method are reliable. Thermodynamic parameters (Δ H, Δ S, Δ G ) are calculated.